2005
DOI: 10.1021/ic050278y
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I) Coordination Polymers Containing Heteroditopic Ureidopyridine Ligands:  The Role of Ligand Isomerism, Hydrogen Bonding, and Stacking Interactions

Abstract: New silver (I) coordination polymers has been successfully designed and synthesized using heteroditopic ureidopyridine ligands 1 and 2 via a combination of coordinations bonds, hydrogen bonding, and pi-pi stacking interactions. This study shows an example of the orientation of the pyridine nitrogen relative to the urea moiety (4-substituted, 1, or 3-substituted, 2), used to control the packing of resulting crystalline coordination polymers. The ureidopyridine ligands present some flexibility because of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…High values of K p and K 2 indicate strong association via H-bonding, while high values of the ratio K p /K 2 are related to the cooperativity of the self-association process. Calculation of the association constants revealed that the strength of the self-association of compound 1 and the process cooperativity are both decreased, when compared with the values determined for the bis-aromatic compound 1 [37] (Fig. 3a).…”
Section: Precursor 1 and Membrane Materials Characterizationsmentioning
confidence: 68%
See 1 more Smart Citation
“…High values of K p and K 2 indicate strong association via H-bonding, while high values of the ratio K p /K 2 are related to the cooperativity of the self-association process. Calculation of the association constants revealed that the strength of the self-association of compound 1 and the process cooperativity are both decreased, when compared with the values determined for the bis-aromatic compound 1 [37] (Fig. 3a).…”
Section: Precursor 1 and Membrane Materials Characterizationsmentioning
confidence: 68%
“…moieties known to bind metal cations (i.e. Li + ) [36] and the anions, respectively [37,38]; (2) the supramolecular guiding interaction is the urea head-to-tail H-bond association, [35,38] reminiscent with the amide moiety's H-bonding in proteins, (3) the ureidopyridyl residues are covalently bonded to triethoxysilyl groups allowing to transcribe the self-organized superstructures into the hybrid materials by sol-gel process [13,14]. 1 H NMR dilution experiments showed the strong downfield shifts of NH alif (Dd = 0.82 ppm) or NH arom (Dd = 2.2 ppm) protons upon increasing concentration of 1, which is indicative of self-association through the intermolecular hydrogen bonding in CDCl 3 (Fig.…”
Section: Precursor 1 and Membrane Materials Characterizationsmentioning
confidence: 99%
“…For biological and related applications, see: Dougherty (1996); Meyer et al (2003); Ma & Dougherty (1997). For examples of tubular superstructures, see: Barboiu et al (2003); Blondeau et al (2005); Fromm & Bergougnant (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…In the L ligand, the DAT group can donate up to three H-bonding acceptors and four H-bonding donors, also, both the triazine ring and the imidazole ring have the p-interaction abilities. It is expected that the L ligand could involve in strong supramolecular interactions with other components, such as counteranions and solvents, which may exert profound effects in the self-assembly process and the architectures of the final products, especially in the Ag(I) system due to the modest stereochemical preferences of the Ag(I) ion [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%